The Role of Dco in Drosophila Haematopoiesis - Jonátová, Lucie (Jihočeská univerzita, 2013)
Point mutations found in human breast cancer samples introduced into the Drosophila dco gene affect the Drosophila haematopoiesis. I described different haematopoietic phenotypes in such mutants and tested their connection with the Toll and the JAK/STAT signalling pathways.
The Role of Dco in Drosophila Haematopoiesis
Keywords: dicsc overgrown; haematopoiesis; cellular immunity; cancer; dicsc overgrown; haematopoiesis; cellular immunity; cancer